Comparative study between corticosteroids and colchicine effect on interleukin-6 and Krebs-von-den Lungen-6 in treatment of post covid pulmonary fibrosis - Mohamed A. E. G. Bedir; Fawzy A. E. Elemery; Mohamed T. A. Elghafar; Mohamed Torky (Egyptian Journal of Chest Disease and Tuberculosis, 2024)
Background Interstitial lung diseases (ILDs) involve a diverse range of over 200 lung disorders, constituting a vast group of diseases. This study aimed to compare Corticosteroids and Colchicine in the treatment of post-covid pulmonary fibrosis (PC19-PF) through the assessment of effects of these drugs on some biomarkers as interleukin-6 (IL6) and Krebs-von-den Lungen-6 (KL6).